Effect of buyer type on market participation of smallholder farmers in northern Ghana - Mzyece, Agness (Kansas State University, 2016)
Transaction costs, one of the most significant barriers to market participation, may vary by buyer type. Depending on who a farmer sells their produce to, they may alter their potential transaction costs consequently influencing their market participation. This study examines the effect of buyer type on smallholder market participation in Northern Ghana where poverty is still endemic and often exacerbated by fewer opportunities for commercialization such as limited access to markets. The analysis is based on data from the agriculture production survey conducted in 2013 and 2014 and the Population based Survey conducted in 2012 in northern Ghana. Analysis is performed using the Double Hurdle approach to control for self-selection bias, ensure more flexibility on the variables affecting the decision to sell and how much to sell as well as to provide unconditional effects of the variables on market participation. The results reveal greater market participation of cash crop producing farmers than those producing a lower value food crop - Maize. The results also show that farmers selling to aggregator-type middlemen and other buyers have a propensity to sell more. The aggregators and ‘other buyers’ buy in bulky, offer lower prices and are associated with lower transport, loading and offloading costs than consumers. Farm output, access to information and price also have a significant positive impact on intensity of market participation. These findings support policy initiatives such as supporting aggregator-type middlemen, increasing the provision of information, promotion of cash crops as well as supporting more interventions focusing on increasing production and yields.
Keywords: Buyer type; Transaction costMarket participation